Molecular Mechanisms of Synaptotoxicity and Neuroinflammation in Alzheimer’s Disease - Marttinen, Mikael; Takalo, Mari; Natunen, Teemu; Wittrahm, Rebekka; Gabbouj, Sami; Kemppainen, Susanna; Leinonen, Ville; Tanila, Heikki; Haapasalo, Annakaisa; Hiltunen, Mikko (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder, which is clinically associated with a global cognitive decline and progressive loss of memory and reasoning. According to the prevailing amyloid cascade hypothesis of AD, increased soluble amyloid-β (A) oligomer levels impair the synaptic functions and augment calcium dyshomeostasis, neuroinflammation, oxidative stress as well as the formation of neurofibrillary tangles at specific brain regions. Emerging new findings related to synaptic dysfunction and initial steps of neuroinflammation in AD have been able to delineate the underlying molecular mechanisms, thus reinforcing the development of new treatment strategies and biomarkers for AD beyond the conventional Aβ- and tau-targeted approaches. Particularly, the identification and further characterization of disease-associated microglia and their RNA signatures, AD-associated novel risk genes, neurotoxic astrocytes, and in the involvement of complement-dependent pathway in synaptic pruning and loss in AD have set the outstanding basis for further preclinical and clinical studies. Here, we discuss the recent development and the key findings related to the novel molecular mechanisms and targets underlying the synaptotoxicity and neuroinflammation in AD.